DAYA MAKAN, DIAPAUSE DAN MOBILITAS KEONG MAS (POMACEA CANALICULATA) PADA BERBAGAI KEDALAMAN AIR - Bunga, Jacqualine Arriani; Wagiman, Franciskus Xaverius; ., Witjaksono; Sidadolog, Jafendi Hasoloan Purba (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2016)
Feeding rate, aestivation and mobility of golden snails (Pomacea canaliculata) at different depths of water. The research was studied in Malaka District, East Nusa Tenggara Province, during the dry and the rainy season (October 2014 - March 2015). Studies on capacity of damage to the Ciherang rice seedlings were carried out for three weeks. The size of snails used in this experiment was 11-20; 21-30; and 31-40 mm. The numbers of seedlings that were planted were 3, 6, 9, 12, 15, 18 and 21 seeds. The treatments were repeated 5 times. The numbers of seeds which are damaged by the snails then were tabulated and analyzed. Snails with the size of 11-20 mm damaged the seeds in 31.67%, followed by snails with the size of 21-30 mm and 31- 40 mm with potency of damaging were 64.76% and 97.38%, respectively. The size of snails affects the level of damage to rice seedlings when transplanting. Study about aestivation was conducted in five villages, namely Kamanasa, Wehali, Umakatahan, Harekakae and Kletek when the rice fields were fallow. The observation point was observed at the corner of the dike and along the dike, evaluated every 10 meters away. The results showed snails aestivate when the fields were dry. Studies on snailâs mobility conducted on the experiment arena on the mud in buckets, which planted with 20 paddy seedlings. The treatment depth of puddles in the experiment were without puddles, half, the same height and twice the height of snails shell. The treatments were repeated 10 times. Measurement of snailâs mobility was performed routinely every 2 hours, observed from the beginning when the snails were placed for 24 hours in advance. The results showed that the depth of the water significantly affected the mobility of snails. Without puddles, the mobility of snails was severely hampered in the mud. The mobility of the juvenile was significantly higher than the imago. The implication of this study was benefit to that the regulating the level of water in the paddy field which is known as an appropriate effective technology and for controlling the attack of the golden snails.